French language learning strategies among beginner-level learners of a Public University in central Peninsula Malaysia during Covid-19 - Hamsan, Hamzah; Abdul Jabar, Mohd Azidan; Abdul Halim, Hazlina (Human Resource Management Academic Research Society, 2023)
This study aims to describe the students' language learning strategies in learning French throughout the new learning norm due to COVID-19. A total number of 203 beginner learners from 9 different classes participated in this study. All classes were held online as part of the Standard Operating Procedure (SOP) to curb the spread of COVID-19. Oxford's (1990) SILL questionnaire (Strategy Inventory for Language Learning) version 7.0 was distributed online via Google Forms to observe learners' language learning strategies. The acquired data were analysed using the Statistical Package for the Social Sciences (SPSS) software and then classified to a certain level of SILL Profile. The result revealed that the Metacognitive Strategies are students' most frequently employed language learning strategies, with a mean score of 3.76. (classified as High level). Subsequently, with a mean score of 3.20, the students' least often used strategy is Compensation Strategies (classified as Medium level). Hopefully, this research will assist learners in learning French in different learning settings. The results of this study show that respondents supervise and plan their learning very well because they had prior experience learning Malay, English, and Arabic. Conversely, respondents lack the mastery to guess the meaning of words from context and struggle to perceive non-verbal communication to understand certain words or explanations because the online teaching and learning platform limits their eye contact during classes. Hopefully, students can improve their French language learning by incorporating more language learning strategies to make online learning more efficient.